Sosialisasi Media Audiovisual Terhadap Perkembangan Belajar Auditorial Anak di SMA Swasta Nurul Ilmi Padangsidempuan Tahun Pelajaran 2023-2024 - Elnila Caniago; Fita Delia Gultom (Jurnal Transformasi Pendidikan Indonesia, 2024)
The learning program with curriculum changes is the government's effort to overhaul education by the government to overcome problems in schools. Among them is giving birth to an independent curriculum as a new curriculum and circulating it in the world of education. An independent curriculum is a curriculum that is carried out by directing teachers to provide freedom of learning style to students. There are 3 learning styles, namely visual learning style, audio learning style and kinesthetic learning style. In reforming learning with an independent curriculum, learning media is also needed to encourage and motivate students to learn. This is what makes teachers must have expertise and creativity in managing learning. Media as intermediaries used in conveying learning material must be understandable to students and quickly provide opportunities for students to manage learning more quickly. An independent curriculum with differentiated learning will certainly be achieved more quickly with the help of learning media. Community service outreach carried out at Nurul Ilmi Padangsisdempuan High School can provide assistance to teachers and students in developing an auditory learning style through audiovisual media in the 2023-2024 academic year.